2012
DOI: 10.1080/14703297.2012.728876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of video podcasting on psychomotor and cognitive performance, attitudes and study behaviour of student physical therapists

Abstract: Purpose: Multimedia is an effective tool to teach psychomotor skills to health care students. Video podcasting is a next step as educators seek methods to present psychomotor skills efficiently. The purposes of this pilot study were (1) compare the effectiveness of video podcasting to live demonstration for teaching psychomotor skills to Doctor of Physical Therapy (DPT) students; (2) examine students' attitudes toward podcasts and (3) examine study behaviour of DPT students. Methods: Faculty developed podcasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 15 publications
1
41
0
2
Order By: Relevance
“…[10,11] An educational video is a versatile tool that can be used to support professors in the classroom or in a simulation laboratory or, at a distance, through the internet [4] or mobile devices [12] to expand access to knowledge. This tool is a practical method, with a good cost-benefit profile and the scenes can be watch multiple times, as many times as necessary [13][14][15][16][17] and can help the students in acquiring new skills and their learning process. [11] The three steps to develop a video are: pre-production, production and post-production.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] An educational video is a versatile tool that can be used to support professors in the classroom or in a simulation laboratory or, at a distance, through the internet [4] or mobile devices [12] to expand access to knowledge. This tool is a practical method, with a good cost-benefit profile and the scenes can be watch multiple times, as many times as necessary [13][14][15][16][17] and can help the students in acquiring new skills and their learning process. [11] The three steps to develop a video are: pre-production, production and post-production.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant differences in scores for the podcast condition as compared to in-person condition. The authors did, however, note neither condition resulted in high examination scores (Moore & Smith, 2012). Regarding student preferences, the authors reported students felt inperson instruction and podcasts were each beneficial for learning with several students suggesting that the use of combined methods may be best for learning (Moore & Smith, 2012).…”
Section: Combined Instructional Methodsmentioning
confidence: 95%
“…While traditional lecturing still remains the predominant teaching approach used for large student groups, the incorporation of educational videos has now become an important part of the curriculum, providing an important content-delivery tool in many flipped, blended and online classes (Brame, 2016). In addition, several meta-analyses have shown that technology can actively enhance learning (Means et al, 2010;Schmid et al, 2014), and numerous other studies have shown that video, specifically, can be a highly effective educational tool (Allen and Smith, 2012;Kay, 2012;Stockwell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%